Chickpea flour in gluten-free baked products - Kanai , Rafaela Soares dos Santos; Souza , Bianca de; Shirai, Marianne Ayumi (Seven Editora, 2023)
The market for gluten-free products has been growing and its main objective is to attend people with celiac disease or allergies related to gluten consumption. The treatment of this disease consists of adopting a gluten-free diet, which is mainly present in wheat, barley and rye. However, replacing wheat flour in the preparation of bakery products remains a challenge for the food industry and research related to the development of new gluten-free products is still necessary. In this context, chickpea flour has highlighted as a potential ingredient in the formulation of gluten-free bakery products, due to the significant concentration of proteins, dietary fiber and micronutrients. This chapter aimed to carry out a literature review on the production and application of chickpea flour in bakery products such as bread, biscuits and cakes. The composition of chickpea, production of chickpea flour and examples of research that applied chickpea flour in bakery products were described. DOI:https://doi.org/10.56238/alookdevelopv1-094